Comparative Spatial Assessment of Trace Metal(loid) Pollution in the Sediments of the Lower Olifants River Basin in South Africa - Addo-Bediako, Abraham (Frontiers in Environmental Science, 2022)
Globally, many freshwater ecosystems are facing chemical pollution from both natural and anthropogenic sources. The Olifants River Basin in South Africa is experiencing degradation due to mining, industrial, agricultural and domestic effluents. The impacts of these activities coupled with climate change is likely to shift the hydrological cycle that may increase accumulation of toxic chemicals in the sediments. The aim of the study was to assess the contamination of As, Cr, Cu, Pb, Fe, Mn, Ni, Pb and Zn in the sediments collected at the upstream, midstream and downstream of four rivers of the Lower Olifants River Basin; the Blyde, Mohalpitsi, Ga-Selati and Steelpoort rivers. The results showed that the highest concentrations of most of the trace metal(loid)s assessed were from the Steelpoort River followed by the Blyde River. Significant diﬀerences in metal concentrations were found across study sites and rivers. When compared with sediment quality guidelines, the concentrations of As, Cr, Cu and Pb exceeded the guideline values across the different rivers. Using enrichment factor (EF) and geo-accumulation index (Igeo), some of the sediments were severely enriched and extremely contaminated respectively with As, Cr, Ni and Pb. The metal(loid) concentrations indicated deterioration of sediment quality and possible secondary pollution in the water. This may risk the lives of aquatic biota and humans, especially rural communities that rely on these rivers for drinking water. The findings provide baseline information for effective management control of metal(loid) pollution in the Olifants River Basin.